2020
DOI: 10.1515/nleng-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature-dependent properties on a gravity-driven thin film along inclined plate

Abstract: A numerical investigation into the effect of temperature-dependent fluid properties on the thin film flow along an inclined heated plate is presented. The equations governing the coupled flow and heat transfer are formulated based on couple stress non-Newtonian model. Solutions of the coupled nonlinear differential equations are tackled numerically by using the combination of shooting method and the Fehlberg-Runge-Kutta method. Findings are presented graphically and discussed precisely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ferdows et al 30 found that conjugate numbers related to concentration and thermal minimizes the stream function in their analysis on nanofluid flow through horizontal plate immersed in Darcy porous medium. Adesanya et al 31 investigated the impact of temperaturedependent parameters including thermal conductivity on thin-film flow past (heated) tilted plates. Recently, Rao et al 32 and Endalew and Sarkar 33 considered the same geometry and inspected various fluid flows with parameters, such as magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Ferdows et al 30 found that conjugate numbers related to concentration and thermal minimizes the stream function in their analysis on nanofluid flow through horizontal plate immersed in Darcy porous medium. Adesanya et al 31 investigated the impact of temperaturedependent parameters including thermal conductivity on thin-film flow past (heated) tilted plates. Recently, Rao et al 32 and Endalew and Sarkar 33 considered the same geometry and inspected various fluid flows with parameters, such as magnetic field.…”
Section: Introductionmentioning
confidence: 99%